Bimetallic electronic effects of Mn-doped Ni-MOF shuttle-like nanosheets remarkably enhance the supercapacitive performance. Issue 22 (10th October 2022) - Pan, Yifan; Gao, Dongyan; Dang, Yupeng; Xu, Pengcheng; Han, Dandan; Liu, Changling; Wei, Yen; Yang, Yanru
Abstract : We explored a new class of binder-free Mn doped Ni-based MOFs nanosheets through a polarity-induced solution-phase method for HSCs. The relationship between the electronic structure and the electrochemical activity has been further identified. Abstract : Metal–organic frameworks (MOFs) with bimetallic centers are considered as promising electrode materials for supercapacitors due to the large specific surface area and potential redox sites. In this work, the internal structure evolution, electron transfer in the metal center, and the mechanism of action of the Mn dopant to enhance conductivity in electrochemical processes are discussed. Density functional theory (DFT) calculations show that the introduction of Mn ions greatly reduces the band gap of the Ni-MOF and increases the carrier concentration, confirming the electron transfer process of electrons from Ni 2+ to Mn 2+ through the bridging oxygen. Therefore, the optimal NiMn-MOF produces an impressive specific areal capacity of 1.89 mA h cm −2 at 1 mA cm −2 . Meanwhile, a hybrid supercapacitor (HSC) based on the NiMn-MOF electrode and activated carbon (AC) can output a high specific energy of 67.5 W h kg −1 at a specific power of 84.5 W kg −1 with excellent cycling stability (capacity retention of 94% after 10 000 cycles). Taking advantage of the high-energy storage properties of the NiMn-MOF//AC supercapacitor device, a solar power generation system is further integrated for self-powered portable electronic applications. This work broadens the applicability of activity prediction for bimetallic MOF electrode materials with high electrochemical performance.